2021
DOI: 10.1002/prp2.767
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐HT2C receptor as a therapeutic target for alcohol and methamphetamine use disorders: A pilot study in treatment‐seeking individuals

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Next, we wanted to ask: how does an insult that disrupts social and arousal behaviors impact the BNST 5HT2c and LHb 5HT2c systems? Studies in humans and animal models suggest that a history of alcohol consumption reduces social behaviors and increases anxiety-like behaviors, which may involve alcohol-induced adaptations in LHb and/or BNST 5HT 2c receptor expression and signaling 22 , 24 , 25 , 27 .To investigate this possibility, we subjected mice to three weeks of DiD, and then after one week of abstinence assessed their behavior in the 3-chamber sociability task, the open field test, and the acoustic startle test (Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we wanted to ask: how does an insult that disrupts social and arousal behaviors impact the BNST 5HT2c and LHb 5HT2c systems? Studies in humans and animal models suggest that a history of alcohol consumption reduces social behaviors and increases anxiety-like behaviors, which may involve alcohol-induced adaptations in LHb and/or BNST 5HT 2c receptor expression and signaling 22 , 24 , 25 , 27 .To investigate this possibility, we subjected mice to three weeks of DiD, and then after one week of abstinence assessed their behavior in the 3-chamber sociability task, the open field test, and the acoustic startle test (Fig. 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, METH has been reported to interact with the re-uptake of 5-HT, resulting in an acute increase in extracellular level of 5-HT, which, in addition to dopamine, is a key mechanism underlying the drug addiction ( 37 ). Moreover, a recent study reported that the withdrawal syndrome following the termination of drug addiction is also associated with profound changes in 5-HT activity ( 38 ). Leucyl-isoleucine is involved in leucine biosynthesis, and mutations in leucine-rich kinases are the common causes of Parkinson’s disease, leading to dopamine neuron loss and motor dysfunction through abnormal increases in neuronal protein synthesis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been progress in developing several selective 5-HT2C agonists, which have been investigated as potential therapeutics for the treatment of multiple psychiatric disorders, particularly impulse-related disorders such as SUDs (Higgins et al, 2013;Campbell et al, 2021).…”
Section: The 5-ht2c Receptor As a Therapeutic Target For Substance Us...mentioning
confidence: 99%